Perceptions of and challenges faced by primary healthcare workers about preconception services in rural India: A qualitative study using focus group discussion - Chutke, Amruta Paresh; Doke, Prakash Prabhakarrao; Gothankar, Jayashree Sachin; Pore, Prasad Dnyandeo; Palkar, Sonali Hemant; Patil, Archana Vasantrao; Deshpande, Aniruddha Vinayakrao; Bhuyan, Khanindra Kumar; Karnataki, Madhusudan Vaman; Shrotri, Aparna Nishikant (Frontiers in Public Health, 2022)
Background: Providing preconception care (PCC) through health care workers at the primary health care level is a crucial intervention to reduce adverse pregnancy outcomes, consequently reducing neonatal mortality. Despite the availability of evidence, this window of opportunity remains unaddressed in many countries, including India. The public health care system is the mainly accessed in rural and tribal Indian population. It is important to know the health care providers (HCP) perceptions about PCC. The study aimed to identify barriers and suggestions for framing appropriate strategies for implementing PCC through public health services. Methods: The authors conducted this qualitative study using focus group discussions with 45 health workers in four blocks of Nashik district. The transcribed discussions were analyzed in MAXQDA software using the Social-Ecological Model (SEM) as an initial coding guide, including four levels of factors (intrapersonal, interpersonal, community, and institutional factors) that influenced PCC. Results: HCP had some knowledge about PCC, limited to adolescent health and family planning services. The interpersonal factors included heavy workload, stress, lack of support and co-operation and paucity of appreciation and motivation. The perceived community factors included poverty, migration, poor knowledge, lack of felt need, the influence of older women of the household, low male involvement, and myths and misconceptions regarding PCC. The identified institutional factors were lack of human resources, specialized services, logistics, and challenges in delivering adolescent health and family planning programs. HCPs recommended need of program specific guidelines, training and capacity building of human resource, un-interrupted supply of logistics and a unique educational community awareness drive supporting preconception care services. Conclusion: Multi-level factors of the SEM influencing the PCC services should be considered for framing strategies in the implementation of comprehensive PCC as a part of a continuum of care for life cycle phases of women.